The Use of Plants as Foodstuffs, Scent Enhancers and Dyes in Meukek District, South Aceh Regency - Retcia Aisa; Wardiah Wardiah; Hasanuddin Hasanuddin; Cut Nurmaliah; Dewi Andayani (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
The study entitled The Use of Plants as Foodstuffs, Flavour Enhancers and Food coloring in Meukek District, South Aceh District, was conducted in August Sd. September 2019. This study aims to determine: (1) plant species used for food, flavour enhancers and colorants (2) plant parts used as food ingredients, flavourenhancers and food coloring (3) how to use plants for food, flavour enhancer and food coloring. This type ofresearchis a descriptive analysis with a qualitative approach.This researchwasconducted in the District of Meukek, South Aceh Regency. This research uses the RRA (Rapid Rular Appraisal) method. Data analyzed directly. Basedontheresultof the study there were 95 species of plants from 41 families (which are used for food for 65 species, aroma enhancer 30 species and coloring 10 species), there are several species that are used more than one utilization group. The parts/organs of plants that are widely used as food are fruit organs (42%) and those with little interest (1%). For flavor enhancers, the most widely used organs are leaves (11%), and those with few stems (1%), skin (1%). As a coloring agent, the most widely used plant organs are fruit (4%), and small rhizomes (1%). The use plant that are usedas food is by cooking or directly consumed. The use plant as a scent and coloring enhancer that is by mixing into food or cooking ingredients. The conclusions of this study are plants that have the potential as food ingredients, flavour enhancers and food coloring in Meukek District are quite abundant and their availability in nature.Keywords:Foodstuffs, Flavour enhancers, Food coloring, Meukek District.Penelitian yang berjudul Penggunaan Tumbuhan Sebagai Bahan Pangan, Penambah Aroma dan Pewarna di Kecamatan Meukek Kabupaten Aceh Selatan telah dilaksanakan pada bulan Agustus Sd. September 2019. Penelitian ini bertujuan untuk mengetahui: (1) Spesies tumbuhan yang digunakan untuk bahan pangan, penambah aroma dan pewarna (2) Bagian tumbuhan yang digunakan sebagai bahan pangan, penambah aroma dan pewarna (3) cara pemanfaatan dari tumbuhan untuk bahan pangan, penambah aroma dan pewarna. Jenis penelitian ini adalah analisis deskriptif dengan pendekatan kualitatif. Penelitian ini dilaksanakan di Kecamatan Meukek Kabupaten Aceh Selatan. Dengan menggunakan metode RRA (Rapid Rural Appraisal). Data dianalisis secara langsung. Berdasarkan hasil penelitian terdapat 95 spesies tumbuhan dari 41 familia (yang digunakan untuk bahan pangan 65 spesies, penambah aroma 30 spesies dan pewarna 10 spesies) terdapat beberapa spesies yang dimanfaatkan lebih dari satu kelompok pemanfaatan. Bagian tumbuhanyang banyak digunakan sebagai bahan pangan yaitu organ buah (42 %) dan yang sedikit bunga (1%). Untuk penambah aroma, organ yang banyak digunakan adalah daun (11%), dan yang sedikit batang (1%), kulit (1%). Sebagai pewarna, organ tumbuhan yang banyak digunakan adalah buah (4%), dan sedikitrimpang (1%). Penggunaan tumbuhan yang digunakan sebagai bahan pangan yaitu dengan cara dimasak atau di konsumsi secara langsung. Pengunaan tumbuhan sebagai penambah aroma dan pewarna yaitu dengan cara di campurkan kedalam bahan makanan atau masakan. Simpulan penelitian ini adalah tumbuhan yang berpotensi sebagai bahan pangan, penambah aroma dan pewarna di Kecamatan Meukek cukup melimpah dan ketersediaanya di alam.Kata kunci: Bahan Pangan, Penambah Aroma, Pewarna, Kecamatan Meukek.